Behring Sea: memoranda on questions 1 to 5 [electronic resource]. - Great Britain. Foreign Office. ([S.l. : s.n., 1893)
Caption title. Attributed to Great Britain. Foreign Office--A bibliography of British Columbia / by B. J. Lowther. Includes bibliographical references. Electronic reproduction. Mode of access: Internet. 44